An investigation of emotional intelligence and counselling self-efficacy among counsellors-in-training - Mohd Azrin Mohd Nasir; Nor Atikah Mat Ali; Abdul Rashid Abdul Aziz; Suzila Ismail; Farah Nadia Mohd Faudzi (Institute of Advanced Engineering and Science, 2023)
The challenges faced by the counsellors-in-training are enormous. Therefore, investigating emotional quotient (EQ) and counselling self-efficacy among counsellors-in-training is crucial. This study aimed to examine the EQ and counselling self-efficacy levels among counsellors-in-training and investigate the relationships between these variables. A total of 373 counselling students from three universities in the Northern Peninsular of Malaysia have participated in this study. This study involved a quantitative method using survey as a data collection technique and also employed a convenience sampling procedure. There were two questionnaires used in this study, namely Bar-On emotional quotient inventory (EQ-i) and counselling self-estimate inventory. The results showed that there was a significant correlation between EQ and counselling self-efficacy which all sub-constructs for both measures are well-associated with each other. In conclusion, these two variables are essential to ensure counselling students would move toward a better developing identity of counsellors-in-training and encourage the growth of professional competency among trainee counsellors in the future. Hence, it is vital for the government to ensure that quality counselling services should be provided for the community to deal with this problem.